Contemporary Strategies in the Management of Civilian Abdominal Vascular Trauma - Karaolanis, Georgios; Moris, Dimitrios; McCoy, C. Cameron; Tsilimigras, Diamantis I.; Georgopoulos, Sotirios; Bakoyiannis, Chris (Frontiers in Surgery, 2018)
The evaluation and management of patients with abdominal vascular trauma or injury requires rapid and effective decision making in these unfavorable circumstances. The majority of these patients arrive at trauma centers in profound shock, secondary to massive blood loss, which is often unrelenting. Moreover, ischemia compartment syndrome, thrombosis, and embolization may also be life threatening and require immediate intervention. To minimize the risk of these highly possibly mortal complications, early understanding of the disease process and rapid therapeutic intervention are necessary. In the literature, the management of acute traumatic vascular injuries is restricted to traditional open surgical techniques. However, surgeons face often a potentially contaminated field, which renders the placement of prosthetic grafts inappropriate. Currently, however, there are sparse data on the management of vascular trauma with endovascular techniques. The role of endovascular technique in penetrating abdominal vascular trauma, which is almost always associated with severe active bleeding, is limited. It is worth mentioning that hybrid operating rooms with angiographic radiology capabilities offer more opportunities for the management of this kind of injuries by either temporary control of the devastating bleeding using endovascular balloon tamponade or with embolization and stenting. The abdominal vascular trauma continues to exist however, open and endovascular technique continue to evolve giving us encouraging messages for the near future.